Identification of Ralstonia solanacearum causing bacterial wilt disease in Terung Asam (Solanum lasiocarpun Dunal) - Sharaman, Farah Eziana; Pakasa, Muhammad Harith Iskandar; Saupi, Noorasmah; Abu Bakar, Fauziah (African Science Publications, 2024)
Terung asam (Solanum lasiocarpum Dunal) or locally known as Terung Dayak is the most popular native vegetable in Sarawak. Its popularity can be witnessed by the fact that it has been widely planted throughout the state by local farmers. However, the farmers have been experiencing massive yield losses caused by a wilting disease directly attributed to a pathogen known as Ralstonia solanacearum. R. solanacearum is one of the most dreadful pathogens because it has a broad host range and causes lethal wilting to plants.